The Land of Stories: Grimm Warning - Book 3 - Colfer, Chris 1990-; Dorman, Brandon (New York, 2014)
After thirteen-year-old Conner returns to the Land of Stories and reunites with his twin sister, Alex, who is training to become the next Fairy Godmother, war breaks out in the fairy-tale world.
"Book 3."
830L
Accelerated Reader AR
Keywords: Characters and characteristics in literature; Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; Fairy tales; Characters in literature; Fiction; Magic; Fiction; Brothers and sisters; Fiction; Twins -- Fiction; War -- Fiction; Youths writings; Fairy tales